Cauliflower (Brassica oleraceavar. botrytis L.) Production Applied with Carabao Manure: Effects on Growth and Yield - Tuan, Leah C. (International Journal of Environment, Agriculture and Biotechnology, 2019)
Utilization of carabao manure as a sustainable approach on nutrient management for cauliflower production was studied for three months between the months of October 2016 to January 2017 at the University Demo Farm, University of Eastern Philippines, Main Campus, University Town, Catarman, Northern Samar, Philippines. The main objective was to determine the effect of carabao manure on the growth and yield of cauliflower. Carabao manure preparations included dried carabao manure, administered at 1.0 kg and 1.5 kg levels boosted with manure tea. Growth and yield performance of cauliflowers were significantly influenced by dried carabao manure applications boosted with manure tea application. Better performance were observed in plants treated with 1.5 kg dried carabao manure than with 1.0 kg was evident on the parameters evaluated, indicative of the nutrient sufficiency of the bio fertilizer. Carabao manure, a farm waste product, an untapped resource, has been proven to be an effective, safe and an economical bio organic fertilizer. A commodity capable of becoming a promising industry; a lowly resource, but if given enough attention can “turn dust into gold” and effect significant changes in the lives of many sort.